Building Climate Resilient Agriculture in Caribbean Countries: The Commonwealth of Dominica - Hayman, Alicia (Inter-American Institute for Cooperation on Agriculture (IICA), 2023)
Agriculture is the second-largest sector in Dominica, contributing between 11.5% and 15.2% of the country's GDP from 2010 to 2020. However, several barriers to implementing the country's NDCs have been identified, including limited availability of data, weaknesses in the institutional environment, inadequate financing, weak technology transfer and capacity development, insecurity of tenure, and high reliance on costly imported inputs. The opportunity to enhance climate ambition from the agriculture sector lies in reducing emissions from enteric fermentation and manure management, as well as exploring opportunities in adaptation, agroforestry, and practices beyond the farmgate.